Elliptic flow of identified hadrons in Pb-Pb collisions at root(NN)-N-s=2.76 Tev - Abelev, B.; Adam, J.; Adamova, D.; Aggarwal, M. M.; Agnello, M.; Agostinelli, A.; Agrawal, N.; Ahammed, Z.; Ahmad, N.; Ahmed, I.; Ahn, S. U.; Ahn, S. A.; et al. (Journal of High Energy Physics, 2015)
The elliptic flow coefficient (v(2)) of identified particles in Pb-Pb collisions at root s(NN) = 2.76 TeV was measured with the ALICE detector at the Large Hadron Collider (LHC). The results were obtained with the Scalar Product method, a two-particle correlation technique, using a pseudo-rapidity gap of |Delta eta| > 0.9 between the identified hadron under study and the reference particles. The v (2) is reported for pi(+/-), K-+/-, K-S(0), p+(p) over bar, phi, Lambda+(Lambda) over bar, Xi+(Xi) over bar (+) and Omega(-)+(Omega) over bar (+) in several collision centralities. In the low transverse momentum (p(T)) region, p(T) < 3 GeV/c, v(2)(p(T)) exhibits a particle mass dependence consistent with elliptic flow accompanied by the transverse radial expansion of the system with a common velocity field. The experimental data for pi (+/-) and the combined K-+/- and K-S(0) results, are described fairly well by hydrodynamic calculations coupled to a hadronic cascade model (VISHNU) for central collisions. However, the same calculations fail to reproduce the v(2)(p(T)) for p+(p) over bar, phi, Lambda+(Lambda) over bar, Xi+(Xi) over bar (+). For transverse momentum values larger than about 3 GeV/c, particles tend to group according to their type, i.e. mesons and baryons. The present measurements exhibit deviations from the number of constituent quark (NCQ) scaling at the level of +/- 20% for p(T) > 3 GeV/c.
Keywords: Collective flow; Heavy Ions; Particle correlations and fluctuations